Estimation of a production function with domestic and foreign capital stock - Thomas Ziesemer (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2022)
We estimate a Cobb-Douglas production function distinguishing between a domestic and a foreign capital stock built from data of imported machinery and transport equipment for Brazil. The preferred regression uses log levels estimated by GMM-HAC. Results are that the elasticity of production of foreign capital is about 40% of that of domestic capital, the function has constant returns to scale in capital and labour variables, and human capital and technical change are also highly productive
Keywords: C22; C51; E23; F43; O54; 330; time-series; estimation; production function; open economy; Brazil